Management of Current Pre Eclampsia - Septiani, Hani; Lestari, Lusi; Ariani, Dini (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Introduction & Objective: Preeclampsia and eclampsia remain significant health issues contributing to high maternal and perinatal mortality rates, particularly in developing countries. Preeclampsia, characterized by hypertension, edema, and proteinuria during pregnancy, affects 2% to 8% of pregnancies globally and is a major cause of maternal and fetal death. This study aims to review the current management strategies for preeclampsia to prevent its progression into eclampsia and improve maternal and neonatal outcomes. Method: A literature review was conducted using secondary data sources. Articles were obtained through systematic searches in databases such as PubMed and Google Scholar, using keywords like